A Qualitative Study on Educational Financing: Methods and Goals to Support Learning Quality in Primary Schools - Nur Indah Fitiriani; Laeli Yuliana Ayuningtias; Sutrisno Sutrisno (FKIP - Universitas Riau, 2026)
Educational financing plays a decisive role in ensuring the effectiveness and quality of learning in primary schools. However, disparities in allocation accuracy, utilization efficiency, and accountability mechanisms often limit its optimal impact. This study aims to explore the methods and goals of educational financing management in supporting learning quality using a qualitative approach. A case study design was employed, involving school principals, teachers, and administrative staff as participants. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using interactive qualitative techniques. The findings indicate that structured financing planning, transparent fund allocation, and participatory monitoring significantly contribute to improving learning quality. Empirical evidence shows an increase in the availability of learning resources by 35%, improvement in classroom facility adequacy by 28%, and a 22% rise in student engagement during instructional activities. Furthermore, schools implementing systematic financial management demonstrated more consistent learning outcomes compared to those with less organized systems. In conclusion, effective educational financing management, supported by collaborative and accountable practices, directly strengthens the quality of primary school learning processes.